Europe-in-between through the eyes of Cohen and Dugin - Botić, Jurica (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
Article offers a comparative analysis of the geopolitical approaches from U.S. and Russian geopoliticians, Saul B. Cohen and Alexander Dugin, in determining the position of Europe-In-Between in contemporary World. The article presents a spatial definition of this term, introduced in the scientific literature by F. Tunjić, and an overview of this area in terms of maritime and continental geopolitics through the reflections of the above mentioned geopoliticians. We are also comparing the current geopolitical moment with the tendencies shown in the papers of these authors to determine the future geopolitical developments in the Europe-In-Between.
Keywords: Europe; Evropa; geopolitika; politična geografija